Anisodamine alleviates lipopolysaccharide-induced pancreatic acinar cell injury through NLRP3 inflammasome and NF-κB signaling pathway. (2nd January 2020) - Li, Zheng; Xu, Chunyang; Tao, Yuanzhuo; Liang, Yuji; Liang, Qixian; Li, Junbao; Li, Renwen; Ye, Hongwei
Abstract: Purpose: Anisodamine (An) has anti-inflammatory effects, but its role in acute pancreatitis is still unknown. This study aimed to explore the action mechanism of An pretreatment in lipopolysaccharide (LPS)-induced pancreatic acinar cells, hoping to provide a research basis for the disease treatment. Materials and methods: Pancreatic acinar cells were pretreated with An at different concentrations and then induced by LPS. The viability and apoptosis of the treated cells were measured by Cell Counting Kit-8 and flow cytometry. The releases of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and IL-18 were measured by enzyme-linked immunosorbent assay. The expressions of thioredoxin-interacting protein (TXNIP), apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC), NOD-like receptor protein 3 (NLRP3), Caspase-1, p65, and inhibitor of kappa B alpha (IκBα) in the treated cells were detected by Western blot and quantitative real-time polymerase chain reaction assay. Results: LPS promoted apoptosis of pancreatic acinar cells, suppressed cell viability, increased TNF-α, IL-1β, and IL-18 releases and the expression levels of TXNIP, ASC, NLRP3, Caspase-1, p-p65, and p-IκBα, however, such effects of LPS could be alleviated by An pretreatment with the strongest effect when the concentration of An was set at 100 μg/mL. Moreover, overexpressed NLRP3 aggravated the effects of LPS in pancreatic acinar cells, which could be reversed by pretreatment of 100 μg/mL An. Conclusion: An pretreatment attenuated LPS-induced apoptosis and inflammatory response of pancreatic acinar cells through suppressing NLRP3 and inactivating NF-κB signaling pathway, thus, it could be explored as a potential therapy for treating acute pancreatitis.